ИЗ ОПЫТА ДИСТАНЦИОННОГО ОБРАЗОВАНИЕ В КИТАЕ. FROM THE EXPERIENCE OF DISTANCE EDUCATION IN CHINA (Ustozlar uchun, 2024)
Resume: Getting an education today is one of the most affordable opportunities for a person. And higher education, which was perceived as an exclusive at the end of the 20th century, has long been no cosmic achievement. Thanks to modern technologies, you can get the most up-to-date knowledge, regardless of where in the world you are. Thanks to the Internet, information has become easily accessible and is spreading at a crazy rate. Radio and television broadcasts have been widely used in China for a long time to teach students, which was the first round of development of distance education. In the Chinese capital, back in the early 60s of the last century, the first regional television universities (RTVU) were established, which helped people get the necessary knowledge.